Automated pastures and the digital divide: How agricultural technologies are shaping labour and rural communities. (May 2019) - Rotz, Sarah; Gravely, Evan; Mosby, Ian; Duncan, Emily; Finnis, Elizabeth; Horgan, Mervyn; LeBlanc, Joseph; Martin, Ralph; Neufeld, Hannah Tait; Nixon, Andrew; Pant, Laxmi; Shalla, Vivian; et al.
Abstract: A "digital revolution" in agriculture is underway. Advanced technologies like sensors, artificial intelligence, and robotics are increasingly being promoted as a means to increase food production efficiency while minimizing resource use. In the process, agricultural digitalization raises critical social questions about the implications for diverse agricultural labourers and rural spaces as digitalization evolves. In this paper, we use literature and field data to outline some key trends being observed at the nexus of agricultural production, technology, and labour in North America, with a particular focus on the Canadian context. Using the data, we highlight three key tensions observed: rising land costs and automation; the development of a high-skill/low-skilled bifurcated labour market; and issues around the control of digital data. With these tensions in mind, we use a social justice lens to consider the potential implications of digital agricultural technologies for farm labour and rural communities, which directs our attention to racial exploitation in agricultural labour specifically. In exploring these tensions, we argue that policy and research must further examine how to shift the trajectory of digitalization in ways that support food production as well as marginalized agricultural labourers, while pointing to key areas for future research—which is lacking to date. We emphasize that the current enthusiasm for digital agriculture should not blind us to the specific ways that new technologies intensify exploitation and deepen both labour and spatial marginalization. Highlights: A "digital revolution" is underway in agriculture marked by technologies like sensors, AI, and robotics. Digitalization impacts labour and rural communities across industrial agri-food contexts. New technologies are likely to intensify exploitation and deepen marginalization for most vulnerable. Equitable, non-exploitative agtech needs to be enhanced and foregrounded.